Design and Implementation of Illuminate Doormat using Piezoelectric - Ali, Nur Hafizah; Mohd Jamail, Nor Akmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2023)
The main goal of this project is to design a portable and cost-effective illuminate doormat that can charge a battery when someone steps on it. By producing energy sustainably and storing it for later use, this project offers an alternative to a current product. The concept behind the design and development of this project is around the idea of harvesting energy from wasteful energy sources that produce from such as footsteps. Due to the transfer of weight onto the ground or the surfaces of the road, a person losses energy when walking in the form of impact, vibrations, sound, etc. By conducting four stages of implementation, the first step was selecting the suitable type, size, and arrangement of piezoelectric materials that can generate the maximum amount of electric current needed for the intended application. Then, followed by designing the simulation circuit for the energy-supplying unit of the electrical energy converted and analysing the energy storage device before finally implementing and analysing the hardware performance of this illuminate doormat application. This illuminate doormat has 10 pieces of 27mm piezoelectric ceramic discs that had been connected in a series-parallel arrangement. The connection of these piezoelectric materials is capable of producing an output power energy of 13.3μW. The piezoelectric materials are also arranged in a way that allows them to fully exert the force of footsteps underneath the doormat. The AC voltage was converted to DC voltage by using a full wave diode bridge rectifier with a smoothing capacitor and connected with a voltage regulator and get a constant DC and protect from overvoltage with a maximum output of 3.68V. Then, it is connected to the DC to DC boost converter module to step up the voltage to 12V that sufficient for the 12V lithium-ion rechargeable battery.